2020
DOI: 10.3390/ijms21041500
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Differences in Key Genes and Pathways Regulating Carbon and Nitrogen Metabolism in Cotton Genotypes under N Starvation and Resupply

Abstract: Nitrogen (N) is the most important limiting factor for cotton production worldwide. Genotype-dependent ability to cope with N shortage has been only partially explored in cotton, and in this context, the comparison of molecular responses of cotton genotypes with different nitrogen use efficiency (NUE) is of particular interest to dissect the key molecular mechanisms underlying NUE. In this study, we employed Illumina RNA-Sequencing to determine the genotypic difference in transcriptome profile using two cotton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 80 publications
6
34
0
Order By: Relevance
“…In our study, the differentially expressed genes are mainly involved in the pathways of phenylpropanoid biosynthesis, amino sugar and nucleotide sugar metabolism, cysteine and methionine metabolism, starch and sucrose metabolism, N metabolism and other pathways. In previous report, cotton under N starvation and re-supply treatment, enriched to a pathway similar to the results of our experiment (Iqbal et al 2020). The KEGG pathways revealed that 15 unigenes, including one NRT gene, two NR genes, one NiR gene, two GDH genes, six GS genes and three GOGAT genes, were related to nitrogen metabolism and signi cantly differentially expressed in response to nitrate starvation and a nitrate re-supply treatment (Chen et al 2018).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the differentially expressed genes are mainly involved in the pathways of phenylpropanoid biosynthesis, amino sugar and nucleotide sugar metabolism, cysteine and methionine metabolism, starch and sucrose metabolism, N metabolism and other pathways. In previous report, cotton under N starvation and re-supply treatment, enriched to a pathway similar to the results of our experiment (Iqbal et al 2020). The KEGG pathways revealed that 15 unigenes, including one NRT gene, two NR genes, one NiR gene, two GDH genes, six GS genes and three GOGAT genes, were related to nitrogen metabolism and signi cantly differentially expressed in response to nitrate starvation and a nitrate re-supply treatment (Chen et al 2018).…”
Section: Discussionsupporting
confidence: 90%
“…This indicated that tomato roots in N de ciency state can uptake an adequate supply of nitrate within 24 h of its being N resupplied, which are consistent with earlier reports(Chen et al 2018;Richard-Molard et al 2008). In previous reports, NR activity decreased under N de ciency stress in cotton(Iqbal et al 2020), rice (Sinha et al 2018), and wheat(Sinha et al 2015), which was consistent with the results in this paper. In this study, tomato seedlings after two days of N de ciency, GOGAT genes were up-regulated, while the expression of SlGS, SlNR, and SlNiR genes were down-regulated in tomato roots.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In general, N partitioning between source and sink organs balances N uptake and metabolism in source organs, and transport potential from source to sink organs [ 5 ]. Moreover, the balance between carbon (C) and N is critical to improving N use efficiency (NUE): N levels can significantly affect C fixation, as photosynthetic proteins, such as Rubisco and PEP carboxylase, constitute a large N sink [ 119 ]. Alterations in amino acid phloem loading and unloading can regulate N and C acquisition and metabolism.…”
Section: Transport Function In Carbon Metabolismmentioning
confidence: 99%
“…The authors also suggested the reasonable regulation of C and N metabolism as a way to improve NUE [ 275 ] and the reprogramming of primary and secondary metabolism under the future climatic scenario [ 276 ]. The study in [ 277 ] was carried out to identify the molecular networks of C and N metabolism in cotton. These authors identified several hub genes that might provide novel insights into coordinating C and N metabolism, which could serve as the basis for high NUE.…”
Section: (Multi)-omics Techniques To Study C and N Metabolism In Pmentioning
confidence: 99%